2020
DOI: 10.1002/ejoc.201901814
|View full text |Cite
|
Sign up to set email alerts
|

Joining High Coloration and Fast Color Fading with Photochromic Fused‐Naphthopyrans

Abstract: An easy synthesis of photochromic naphthopyrans with a lactone ring linking the naphthalene core to the pyran double bond is described. UV irradiation (or exposure to sunlight) of these uncolored compounds provide a single photoisomer with an intense orange coloration that returns completely to the initial uncolored state much faster than common naphthopyrans used in commercial photochromic ophthalmic lenses. A polymeric uncolored material doped with one of these lactone‐fused naphthopyrans develops an intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The first approach consists in the synthesis of new photochromic molecules with minimal conformational changes along the photochromic interconversion to minimize the matrix effect. This has been mainly achieved with imidazole-based molecules, [21][22][23][24][25][26][27][28][29][30][31][32][33] prepared by Abe et al, or preventing the formation of the naphthopyrans (transoid-trans) [34][35][36][37][38][39][40][41][42][43] /spirooxazines (trans-merocyanines) 44,45 long-lived isomeric open form, responsible for the slowdown of the ring-closure reaction (oxazines, substituted…”
Section: Introductionmentioning
confidence: 99%
“…The first approach consists in the synthesis of new photochromic molecules with minimal conformational changes along the photochromic interconversion to minimize the matrix effect. This has been mainly achieved with imidazole-based molecules, [21][22][23][24][25][26][27][28][29][30][31][32][33] prepared by Abe et al, or preventing the formation of the naphthopyrans (transoid-trans) [34][35][36][37][38][39][40][41][42][43] /spirooxazines (trans-merocyanines) 44,45 long-lived isomeric open form, responsible for the slowdown of the ring-closure reaction (oxazines, substituted…”
Section: Introductionmentioning
confidence: 99%
“…General mechanism for the photochromic behavior of vinylnaphthofuran 3 a. 7.30 ppm, and OH at 5.07 ppm confirm the phenolic group attached to the carbon C-2. P 3 is then identified as the 4'phenyl-[1,2'-binaphthalen]-2-ol (Figure S28).…”
Section: Structural Elucidation Of Photoproducts P 1 and Pmentioning
confidence: 80%
“…For instance, the reaction of methyl 4-hydroxy-6-methoxy-2-naphthoate with 1,1-diphenylbut-2-yne-1,4-diol, at room temperature, under acid catalysis, gives directly a naphthopyran with a fused lactone ring (Scheme 3). [7,8] Contrary to common thermally reversible photochromic naphthopyrans used in the ophthalmic lenses industry, which generate two colored species, with different thermal stability, under sunlight, these lactone-fused naphthopyrans can only form a single colored photoisomer and thus exhibit a faster color decay in the dark. [9,10] However, we observed that the ester group in the meta position of the naphthol is essential for the formation of the pyranic ring.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Unlike P-type compounds, T-type compounds have faster discoloration and fading rates. These materials include azo copolymers, [3] fusednaphthopyrans, [4] monomer-polymer heterostructures, [5] polyurethane cement composites, [6] WO 3 nanoparticle [7] and so on. It is typically used in aerospace, optical lens, other scientific and technological fields.…”
Section: Introductionmentioning
confidence: 99%